2017
DOI: 10.1007/s10482-017-0864-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional and phylogenetic diversity of cultivable rhizobacterial endophytes of sorghum [Sorghum bicolor (L.) Moench]

Abstract: A diverse group of bacteria colonize the exo- and endo-rhizospheres of sorghum and play a critical role in its tolerance to drought and other abiotic stresses. Two hundred and eighty endophytic bacteria were isolated from the surface-sterilized roots of four sorghum cultivars that were grown on three soil types at three different phenological stages of growth. The isolates were subjected to in vitro screening for their plant growth promoting traits. Out of 280 isolates, 70 could produce Indole 3-Acetic Acid (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 66 publications
1
16
0
2
Order By: Relevance
“…BV152.1. Members of this Gram-positive genus, with the ability to form endospores under harsh environmental conditions, have been isolated from various environments, however, they are often found in soil and in association with plants ( Ouoba et al, 2015 ; Fredsgaard et al, 2017 ; Govindasamy et al, 2017 ; Yan et al, 2017 ). L. fusiformis S9, isolated from the river bank soil sample in India, has been reported to produce glycolipids with surfactant properties, but the identity of the sugar moiety was not confirmed and in contrast to BV152.1 isolate, the unsaturated alkanoic acid was predominant lipid chain ( Pradhan et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…BV152.1. Members of this Gram-positive genus, with the ability to form endospores under harsh environmental conditions, have been isolated from various environments, however, they are often found in soil and in association with plants ( Ouoba et al, 2015 ; Fredsgaard et al, 2017 ; Govindasamy et al, 2017 ; Yan et al, 2017 ). L. fusiformis S9, isolated from the river bank soil sample in India, has been reported to produce glycolipids with surfactant properties, but the identity of the sugar moiety was not confirmed and in contrast to BV152.1 isolate, the unsaturated alkanoic acid was predominant lipid chain ( Pradhan et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The structural composition of endophytic bacterial communities depends on genotype of the host plant, the kind of tissue and the vegetation stage. The species composition may also be significantly influenced by plant stress and soil types (Govindasamy et al 2017;Kumar et al 2017). In our study, we purified 110 isolates with different morphologies from surface sterilized root-tissues of nine genotypes of rice (Oryza sativa L.) grown in alluvial soil of ICAR-IARI research Farm, PUSA campus New Delhi (Annapurna et al 2017).…”
mentioning
confidence: 99%
“…The present study showed that EX2, EN1, EN3, EN5, EN8 and EN9 exhibited multiple plant growth-promoting traits where most of them were endophytic rhizobacteria or rhizobacteria isolates that recovered from interior root tissue of oil palm. The collection of multiple traits from this study was at 20% of the total collection which considerably higher than Govindasamy et al (2017) who found that only 5 bacterial isolates from a total of 280 isolates (1.8%) from sorghum (Sorghum bicolor) rhizosphere were having multiple traits (more than three plant growth promotion traits).…”
Section: Resultsmentioning
confidence: 56%